2014
DOI: 10.1007/s00432-014-1694-3
|View full text |Cite
|
Sign up to set email alerts
|

The clinical relevance and prognostic significance of adenosine triphosphate ATP-binding cassette (ABCB5) and multidrug resistance (MDR1) genes expression in acute leukemia: an Egyptian study

Abstract: In conclusion, the results obtained by the current study provide additional evidence of the role played by these genes as predictive factors for resistance of leukemic cells to chemotherapy and hence treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 35 publications
4
22
1
Order By: Relevance
“…After induction chemotherapy, we found that the more ABC transporters were overexpressed in de devo AML patients, the less chances the patients had of achieving CR. Researchers suggested this phenomenon occurs due to multifactorial regulation, leading to the reduction of intracellular drug concentrations through modulations in drug influx and efflux (12). In addition, previous study proposed that children with AML who expressed more ABC transporters had a lower chance to respond well to therapy (as measured by the percentage of patient having <5% leukemic cells by day 15 of therapy) (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After induction chemotherapy, we found that the more ABC transporters were overexpressed in de devo AML patients, the less chances the patients had of achieving CR. Researchers suggested this phenomenon occurs due to multifactorial regulation, leading to the reduction of intracellular drug concentrations through modulations in drug influx and efflux (12). In addition, previous study proposed that children with AML who expressed more ABC transporters had a lower chance to respond well to therapy (as measured by the percentage of patient having <5% leukemic cells by day 15 of therapy) (18).…”
Section: Discussionmentioning
confidence: 99%
“…Non-remission (NR) was defined as a marrow blasts percentage did not decrease to 25% or below after induction chemotherapy. Early death was defined as death before completion of the induction chemotherapy cycle (12). The patients who reached CR and maintained relapse free survivals (RFS) for >9 months were regarded as good response to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[5] All these results indicated that, ABCB5 expression is closely related to the CSCs-driven cancer, [41,65,67] ABCB5 expressing or not in CRC may represent another drug-resistant mechanism. [68] Therapies target CR-CSCs subpopulation with tumorigenicity and chemotherapy resistance can improve the therapy efficacy in these malignant tumors. [41] Some research suggested that CSC is resistant to radiotherapy, such as, compared with CD133 − tumor cell, the chemotherapy resistance increased in CD133 + human brain glioma stem cell, meanwhile, CD133 + tumor cells presented preferentially activation of DNA damage checkpoint in response to radiotherapy-induced DNA damage and repair.…”
Section: Drug-resistance Of Colorectal Cancer Stem Cellsmentioning
confidence: 99%
“…90 Although the underlying basis for susceptibility is uncertain, analysis of potential glioma susceptibility loci by GWAS has identified variants in chromosome 9p21 near CDKN2A and CDKN2B. 91,92 The glioma candidates are not in the same linkage disequilibrium block as the CDKN2A melanoma gene, but it suggests the possibility that this region may account for shared predisposition to both cancers.…”
mentioning
confidence: 99%
“…[89][90][91] A possible role has also been proposed in oral SCC and leukaemia, and it is overexpressed in almost a third of sporadic oesophageal cancer. 21,92,93 The rare segregating variant in this family (rs193255587) is a splicing mutation, and the effects of this mutation would depend on consequent protein expression and function. Figure 16).…”
mentioning
confidence: 99%